METODE PEMBELAJARAN SNOWBALL DRILLING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII MTs. NEGERI NGADA - Eni Syafitri; Gregorius Taga; Stefania Baptis Seto (Program Studi Pendidikan Matematika, 2021)
This study aims to (1) produce a snowball drilling learning tool for relation and function material for class VIII students of MTs. Negeri Ngada Academic Year 2020/2021; (2) improve learning outcomes through snowball drilling for relation and function material for class VIII of MTs. Negeri Ngada Academic Year 2020/2021. The type of research used experimental research with a quantitative approach. The research procedure began by prepared learning tools included RPP, LKS, THB. After conducted the trial phase, the learning device has meets the requirements for validity, reliability, sensitivity, and was suitable for used in research. Sources of data this research were obtained from student learning outcomes test in the from of pre-test and post-test. The research data were processed using Anacova (analysis of variances) statistical analysis. From the result of the development of learning tools snowball drilling for relation and functions material, a good learning tool is produced. Based on the result of covariance analysis, it was obtained that Fcount = 17.43823 and Ftable = 4.21(Fcount > Ftable) with dk numerator 1 and dk denominator = 27 give a significant value. This shows that the snowball drilling learning method is considered to improve learning outcomes for relation and function material.